PENGARUH ETOS KERJA DAN PERENCANAAN KARIER TERHADAPEFEKTIVITAS KERJAKARYAWAN PADA PT. LG ELEKTRONIK - Achmad Deni Daruri; Kadek Okta Dwi Putra (Sekolah Tinggi Manajemen IMMI, 2018)
Work effectiveness be one of the important element in task execution everyday that must be payed by organizations leaders. organization good/mandate organization that can to produce work effectiveness maximal have a certain quality that can responsive need and society aspiration. successful key in career ripe planning. planning not only made once, but must be done repeat. as does well-being investigation, career even also want cheque according to periodically.This problem formulation: 1) What found work ethic influence towards employee work effectiveness in PT. LG Electronic? 2) What found career planning influence towards employee work effectiveness in PT. LG Electronic ? 3) What found work ethic influence and career planning according to together towards employee work effectiveness in PT. LG Electronic?This watchfulness aim: 1) To detect work ethic influence towards employee work effectiveness in PT. LG Electronic.2) To detect career planning influence towards employee work effectiveness in PT. LG Electronic. 3) To detect work ethic influence and career planning according to together towards employee work effectiveness in PT. LG Electronic.Conclusion: 1) Found influence significant and positive between work ethic towards employee work effectiveness in PT. LG Electronic. This matter is this shows that when does work ethic increase, so employee work effectiveness in PT. LG Electronic also increase electronic or on the contrary. With dimension concept, area and character. 2) Found influence significant and positive between career planning towards employee work effectiveness in PT. LG Electronic. This matter is this shows that when does career planning increase, so employee work effectiveness in PT. LG Electronic also increase electronic or on the contrary. With dimension benefit, function and concept. 3) Found positive influence and significant work ethic and career planning according to together towards employee work effectiveness in PT. LG Electronic. This matter shows that according to together work ethic and career planning can increase employee work effectiveness in PT. LG Electronic. With dimension strategy, quality and competence.